Role of lattice strain in bifunctional catalysts for tandem furfural hydrogenation–esterification. Issue 3 (20th December 2022) - Hashim, Luqman H.; Halilu, Ahmed; Umar, Yahaya Balarabe; Johan, Mohd Rafie Bin; Aroua, Mohamed Kheireddine; Koley, Paramita; Bhargava, Suresh K.
Abstract : This research represents that the bifunctional catalyst (Cu/RHSiO2 –Al–Mg) which has the lowest lattice strain can significantly enhance catalytic reactivity such as the furfural conversion into furfural acetate. Abstract : Furfuryl acetate is a significant value-added chemical with applications in various fields such as the biofuel, food and beverage, and fragrance industries. Furfuryl acetate is commonly prepared via the catalytic hydrogenation–esterification of biomass-derived furfural. This study presents the design and synthesis of highly active bifunctional catalysts that achieve 91.3% furfural conversion. Bifunctional catalysts have recently emerged as exceptional heterogeneous catalysts exhibiting high catalytic activity and product selectivity. However, limited knowledge is available about the role of lattice strain in bifunctional catalysts. Lattice strain can strongly influence catalytic activity by controlling crystal orientation, exposure of crystal facets, and atom rearrangement. Pd, Ni, and Cu-based catalysts were prepared by doping on RHSiO2 –Al–Mg acidic supports to obtain Pd/RHSiO2 –Al–Mg, Ni/RHSiO2 –Al–Mg, and Cu/RHSiO2 –Al–Mg, respectively. Lattice strains of only ∼0.094, 0.124, and 0.357% were observed for Cu/RHSiO2 –Al–Mg, Ni/RHSiO2 –Al–Mg, and Pd/RHSiO2 –Al–Mg catalysts, respectively. This implied that the catalysts' metal sites were 99.991, 99.870, and 99.643% perfect crystals. All synthesized catalysts were active and selective for tandem hydrogenation–esterification of furfural to furfuryl acetate. Interestingly, Cu/RHSiO2 –Al–Mg exhibited the best performance with a turnover frequency of 0.89 h −1 for furfuryl acetate, which was significantly higher than Ni/RHSiO2 –Al–Mg (0.032 h −1 ) and Pd/RHSiO2 –Al–Mg (0.039 h −1 ). Based on catalytic and characterization data, higher lattice strain leads to poor active site reorientation in the catalysts, which affects the rate-limiting step of H2 splitting in the tandem furfural hydrogenation–esterification reaction. Thus, bifunctional catalysts with perfect crystal structure and low lattice strain exhibited higher catalytic activity.